High-temperature corrosion and materials applications - Lai, G. Y. (ASM International, 2007)
George Lai's 1990 book, High-Temperature Corrosion of Engineering Alloys, is recognized as authoritative and is frequently consulted and often cited by those in the industry. His new book, almost double in size with seven more chapters, addresses the new concerns, new technologies, and new materials available for those engaged in high-temperature applications. As we strive for energy efficiency, the realm of high-temperature environments is expanding and the need for information on high temperature materials applications was never greater. In addition to extensive expansion on most of the content of the original book, new topics include erosion and erosion-corrosion, low NOx combustion in coal-fired boilers, fluidized bed combustion, and the special demands of waste-to-energy boilers, waste incinerators, and black liquor recovery boilers in the pulp and paper industry. The corrosion induced by liquid metals is discussed and protection options are presented.